Race and Ethnicity Have a Mixed Effect on the Treatment of Tibial Plateau Fractures. Issue 10 (October 2017) - Driesman, Adam; Mahure, Siddharth A.; Paoli, Albit; Pean, Christian A.; Konda, Sanjit R.; Egol, Kenneth A.
Abstract : Objectives: To determine whether racial or economic disparities are associated with short-term complications and outcomes in tibial plateau fracture care. Design: Retrospective cohort study. Setting: All New York State hospital admissions from 2000 to 2014, as recorded by the New York Statewide Planning and Research Cooperative System database. Patients/Participants: Thirteen thousand five hundred eighteen inpatients with isolated tibial plateau fractures (OTA/AO 44), stratified in 4 groups: white, African American, Hispanic, and other. Intervention: Closed treatment and operative fixation of the tibial plateau. Main Outcome Measurements: Hospital length of stay (LOS, days), in-hospital complications/mortality, estimated total costs, and 30-day readmission. Results: There were no significant differences regarding in-hospital mortality, infection, deep vein thrombosis/pulmonary embolism, or wound complications between races, even when controlling for income. There was a higher rate of nonoperatively treated fractures in the racial minority populations. Minority patients had on average 2 days longer LOS compared with whites ( P < 0.001), costing on average $4000 more per hospitalization ( P < 0.001). Multivariate logistic regression found that neither race nor estimated median family income were independent risk factors for readmission. Conclusions: Although nature of initial injury, use of external fixator, comorbidity burden, age, insurance type, and LOS were independent risk factors for readmission, race and estimated median family income were not. In patients who sustained a tibial plateau fracture, race and ethnicity seemed to affect treatment choice, but once treated racial minority groups did not demonstrate worse short-term complications, including increased mortality and postoperative readmission rates. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.